Investigation of integrated biomass pyrolysis and gasification process for green fuel production. (December 2017) - Im-orb, Karittha; Detchusananard, Thanaphorn; Ponpesh, Pimporn; Arpornwichanop, Amornchai
Abstract: The energy production from biomass has been received closer attention due to an increased concern in greenhouse gas emissions from fossil fuel combustion unit. Gasification is a promising technology used to convert biomass to a synthesis gas. Although the gasification process provides a high amount of synthesis gas, it also consumes high energy, especially in an air separation unit (ASU), which is the largest energy consumer in the process. A design of new biomass conversion process offering lower energy consumption is an interesting topic and focused in this study. The integrated biomass pyrolysis and gasification (IBPG) process, for the co-production of synthesis gas and bio-oil, is investigated using the IBPG model developed in Aspen custom modeler. Rice straw is a considered biomass feedstock. The effects of changes in pyrolysis temperature on the IBPG performance, i.e., product distribution and energy consumption, are investigated. The amount of oxygen required to achieve 98% of char conversion at gasifier is found to decrease as the pyrolysis temperature increases, resulting in the decrease of energy required at ASU. The production rate of synthesis gas and bio-oil derived from IBPG process increase as pyrolysis temperature increases due to the increased volatiles. Comparing with the conventional biomass gasification, although the IBPG process offers lower syngas production rate, it provides additional bio-oil as a valued product. Additionally, the lower amount of waste heat released from IBPG process is found. The IBPG process with high pyrolysis temperature offers a high amount of synthesis gas and bio-oil and releases the low amount of waste heat.